1989
DOI: 10.1159/000168012
|View full text |Cite
|
Sign up to set email alerts
|

Infection of Hemodialysis Catheters: Incidence and Mechanisms

Abstract: Fifty-three consecutive subclavian or jugular hemodialysis catheters inserted into 41 patients were prospectively studied over a period of 8 months in order to determine the incidence of infection and its mechanisms. The intravascular, intradermal and the Y catheter segments as well as both connections were cultured using a quantitative technique for the intraluminal surface. In addition, the intravascular and intradermal portions of the catheter were cultured using a semiquantitative technique for the externa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
23
1
5

Year Published

1996
1996
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(32 citation statements)
references
References 14 publications
3
23
1
5
Order By: Relevance
“…In our study, positive tip semiquantitative cultures were obtained from 10 catheteres (40%), data consistent with findings of Almirall et al (1), 55%. The quantitative procedure showed that 4 catheters (16%) had 10 3 or more CFUs per milliliter, while cultures were negative in 18 (72%).…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…In our study, positive tip semiquantitative cultures were obtained from 10 catheteres (40%), data consistent with findings of Almirall et al (1), 55%. The quantitative procedure showed that 4 catheters (16%) had 10 3 or more CFUs per milliliter, while cultures were negative in 18 (72%).…”
Section: Resultssupporting
confidence: 93%
“…A number of investigators have used this procedure to quantify biofilms and determine the relationship between biofilm formation and bloodstream infection (1). However, this technique will not detect organisms on the inner lumen of the catheter and is unable to detect more than 1,000 CFU per tip (13).…”
Section: Resultsmentioning
confidence: 99%
“…Bacteraemia is a common complication in haemodialysis patients resulting from contaminated vascular access devices [1,7,10,12,13]. The most frequent place for bacterial colonisation is the spine [23], frequently at the thoracolumbar junction.…”
Section: Discussionmentioning
confidence: 99%
“…Bacteraemia is also the first cause of morbidity and mortality in patients under haemodialysis [11]. Bacteraemia usually comes from the vascular contamination by intravenous catheters or punctures of the water-pipe [1,7,10,12,13], with Staphylococcus aureus as the most frequently isolated micro-organism. Very frequently, these patients are elderly, are immunocompromised, and suffer from some other concurrent diseases [9] which presage a high morbidity and mortality rate.…”
Section: Introductionmentioning
confidence: 99%
“…Molecular typing of blood, skin, and catheter hub isolates suggests that most CLABSIs occurring early after line insertion originate from the skin (and are likely insertion-related events), whereas many CLABSIs occurring after the first 1-2 weeks of line placement are related to catheter hub contamination. [2][3][4][5][6][7][8] Most notable CLABSI prevention efforts to date have focused on optimizing insertion practices. 9 While these efforts have successfully decreased CLABSI rates, they have not eliminated preventable CLABSIs.…”
mentioning
confidence: 99%